2018
DOI: 10.4103/ortho.ijortho_195_17
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Free Chemotherapy and Limb Salvage Surgery for Paediatric Osteosarcoma in India

Abstract: Background:Osteosarcoma (OS) is the most common primary malignant tumor of bone. The survival of OS patients has steadily improved from <20% in the early 20th century to around 70% with current treatment. There are very few studies in pediatric OS from India analyzing various aspects of the disease. This study focuses on the clinical profile, treatment options, and their complications and survival outcomes in pediatric osteosarcoma (OS) patients.Materials and Methods:This was a retrospective observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…They analyzed 40 children <14 years, who underwent LSS and used the same chemotherapy regimen as in our study. [9] An interesting observation in our study was that even though our patients received nonmethotrexate containing chemotherapy, the OS and EFS are comparable to those who received methotrexate containing regimens. Methotrexate-based regimens are the standard of care in Europe and North America.…”
Section: Discussionmentioning
confidence: 53%
“…They analyzed 40 children <14 years, who underwent LSS and used the same chemotherapy regimen as in our study. [9] An interesting observation in our study was that even though our patients received nonmethotrexate containing chemotherapy, the OS and EFS are comparable to those who received methotrexate containing regimens. Methotrexate-based regimens are the standard of care in Europe and North America.…”
Section: Discussionmentioning
confidence: 53%
“…Centers reported 5‐year relapse/progression‐free (PFS) survival rates in patients with osteosarcoma ranging from 40% to 68% with various combinations of the other active drugs (Figure 3A,B; Table 3). 7,8,42–61 The initial proof of non‐HDMTX protocols came from the European Osteosarcoma Intergroup (EOI) trials. While the first EOI trial compared two‐drug protocol Adriamycin‐ cisplatin (AP) to AP with HDMTX, the second trial compared AP to a T10‐like multidrug protocol 48,62 .…”
Section: Systemic Therapy Evolution In Osteosarcoma ‐ Lmic Perspectivementioning
confidence: 99%
“…There are only occasional reports on HDMTX in osteosarcoma from India and other LMIC; major oncology centers in India use non‐HDMTX‐based protocols 6,7,52,61,68 . There are challenges associated with mandatory inpatient treatment in high turnover tertiary care cancer centers, while there are concerns related to possible suboptimal dosing, overhydration, and excessive LV administration to mitigate potential toxicities and compensate for inadequate monitoring facilities in peripheral centers using HDMTX.…”
Section: Systemic Therapy Evolution In Osteosarcoma ‐ Lmic Perspectivementioning
confidence: 99%
“…The 3-year survival using a non-HDMTX protocol in osteosarcoma patients was 54.6% in a South Indian study. [7] Successive studies in another tertiary care center demonstrated 32% good responders and a 5-year survival of 50% treated with a protocol without HDMTX. [8][9][10] The "OGS-12" protocol was well tolerated with comparable toxicities.…”
mentioning
confidence: 99%